Evaluasi Supplier dengan Menggunakan Metode Max–Min - Yanti Kusuma (Jurnal Teknik Industri, 2007)
Every company have more than one supplier for the supply of required material. This matter function to improve strength drive a bargain had by company as well as to take care of the availibility of product. Various problem related to supplier always emerge. For example, inappropriate quality of specification and delay of delivery. This situation push importantly of him evaluate supplier periodically for the agenda of getting supplier the bestness. This matter also happened in PT SAI Apparel Industries which producing ready made clothes. Intention of this research was to Choose type of supplier with biggest problem for the PT SAI Apparel Industries and measure performansi of suppliers. There are some methods evaluate supplier able to be used for the election of supplier. But the method seldom involving or joining performance variability at making decision processes. This is matter which necessary for buyer to estimate and put into some type of is calculation to more accurate in evaluating performance of supplier and improve effectiveness at making decision processes. This matter can reach by using approach of Max - Min, which can calculate value of efficiency maximum and minimum of supplier at process evaluate supplier. Later; Then result of this tested by statistic non parametric in identifying homogeneous group of supplier. By using 5 attribute selected by PT SAI Apparel Industries in the evaluation of him, got result of that PT Kahatex is best supplier (performer good), is later; then followed by Persh. YKK JKT, PT.Lucky Print Abadi, and Persh. Bintang Surya.